ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI UNDERPRICING SAHAM: STUDI PADA PERUSAHAAN YANG MELAKUKAN INITIAL PUBLIC OFFERING DI BURSA EFEK INDONESIA PADA TAHUN 2016 – 2019 - SE, Ivana Agustin (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2020)
This study aims to analyze factors that influence stocks underpricing; they are financial leverage, profitability, underwriter reputation, stock offering percentage, and auditor reputation. The object of this study is the stock price of companies making IPO from 2016 to 2019. This research uses purposive sampling method to eliminate the population, resulting in qualified 81 data, which were then analyzed using multiple regression analysis in SPSS 25. This study finds that profitability (ROA) and underwriter’s reputation partially have negative and significant effects on the underpricing. The other independent variables, i.e. (Debt to Equity Ratio, stock offering percentage, and auditor’s reputation) do not have any significant effect on underpricing. This study also proves that all the independent variables simutaneously have a significant effect on underpricing. Keywords: debt to equity ratio, return on asset, underwriter reputation, stock offering percentage, auditor reputation, underpricing.